1992
DOI: 10.1016/0735-1097(92)90501-d
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of thrombolytic and systemic effects of the novel recombinant plasminogen activator BM 06.022 compared with alteplase, anistreplase, streptokinase and urokinase in a canine model of coronary artery thrombosis

Abstract: The thrombolytic and systemic effects of BM 06.022 were evaluated and compared with those of alteplase, anistreplase, streptokinase and urokinase in a canine model of coronary artery thrombosis. BM 06.022 consists of the kringle-2 and protease domains of human tissue plasminogen activator (t-PA) and is unglycosylated because of its expression in Escherichia coli cells. Thrombus formation in anesthetized open chest dogs was induced by electrical injury to the intimal surface of the left circumflex coronary arte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
1

Year Published

1993
1993
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(33 citation statements)
references
References 24 publications
0
32
1
Order By: Relevance
“…These findings are essentially consistent with the mean residence time of YM866 calculated from phar macokinetics in rats (8) and can probably be extrapolated to man. It has been reported that deletion or substitution mutants within the heavy chain had longer half-lives and showed a superior thrombolytic effect than native t-PA in vivo (11,31). We suggest that the superior thrombolytic effect of YM866 can be attributed to its sustained plasma concentration and its greater specific activity and affinity for fibrin.…”
Section: Discussionmentioning
confidence: 63%
“…These findings are essentially consistent with the mean residence time of YM866 calculated from phar macokinetics in rats (8) and can probably be extrapolated to man. It has been reported that deletion or substitution mutants within the heavy chain had longer half-lives and showed a superior thrombolytic effect than native t-PA in vivo (11,31). We suggest that the superior thrombolytic effect of YM866 can be attributed to its sustained plasma concentration and its greater specific activity and affinity for fibrin.…”
Section: Discussionmentioning
confidence: 63%
“…In addition, angiographic data were available in only a proportion of patients, with variable time intervals between thrombolytic therapy and coronary angiography. Thus, although reteplase has been generally associated with earlier, more complete, and sustained reperfusion of the infarctrelated artery as compared with alteplase in animal studies [17,40] and in humans [18,19,21] , its effect in this study population remains unascertained.…”
Section: Limitationsmentioning
confidence: 97%
“…In our work, we engineered a fusion protein consisting of a whole fragment of rPA that is the third generation thrombolytic agent in clinic and a 12-residue fragment of hirudin-PA which docked with N-terminus of rPA via Gly-Gly-Gly. The thrombolytic component in HV12p-rPA shows greater specificity for the thrombus compared with the first and second generation counterparts, including t-PA, staphylokinase, and urokinase [21,22]. In comparison with the structure of t-PA, rPA has deleted Kringle I, EGF, and finger domains, of which two domains facilitate t-PA to bind to the hepatic cell surface receptor, partly elucidating the fast clearance of t-PA in vivo.…”
Section: Discussionmentioning
confidence: 95%